Colonial Archives and the Art of Governance - Stoler, Ann Laura (جماعة, 2017)
Recently, anthropologists engaged in postcolonial studies have increasingly adopted a historical research perspective, and as a result, they are increasingly using archives. However, this use continues to focus on attempts to ‘ditch’ information rather than on an ethnographic reading of the archive. Thus, anthropologists continue to rely on documents—an unsystematic reliance—to confirm colonial inventions, such as certain practices, or to emphasize various cultural claims. However, this type of research focuses on mining the content of documents originating from government committees, reports, and other archival materials, and only rarely does it pay attention to their location in the archive and the unique form of these materials. Researchers must change their perception and examine archives not only as sources of information, but also as objects of research in their own right. Using colonial archival materials from the Dutch East Indies, this article seeks to argue that scholars should examine archives not as sites that are repositories of knowledge, but as sites that produce knowledge, monuments of the state, and also as arenas where the ethnography of the state is done. Such shifts in perception require a deeper examination of archives as cultural agents of the production of ‘facts’, of the production of taxonomic systems in the processes of state formation and authority. Understanding what constitutes the archive, what form it takes, and what the classification and epistemological systems operating within it at a given time signify (and reflect) allows us to examine essential components of colonial politics and state authority. As this article will demonstrate, the archive was the high-tech of the imperial state in the late nineteenth century, and served as a space for the storage of coded beliefs that reflected and testified to the connections between secrecy, law, and power.